Embracing Midlife: Congregations as Support Systems - Baab, Lynne M., (Rowman & Littlefield Publishers, 1999)
This book helps normalize and therefore lessen the fear we might experience during the midlife crisis by educating us about midlife dynamics. This book reduces anxiety in congregations that fear they don't know how to react as it shows ways to explore and respond to midlife issues of loss, difficult relationships, anger, fear, sexuality, paradox and tension, pain, and changing relationship to God. It helps readers learn how to be present with people in midlife transition without feeling that they will be engulfed or that they must solve all midlife problems.